Does shifting from conventional to zero tillage in combination with a cover crop offers opportunities for silage maize cultivation in Flanders?. Issue 6 (1st October 2019) - Landschoot, Sofie; Dewitte, Kevin; Marynissen, Bram; Derycke, Veerle; Latré, Joos; Haesaert, Geert
Abstract: Tillage is an important agricultural practice, influencing the physical, chemical and biological soil characteristics. In this paper the influence of various tillage systems combined with or without a cover crop under different nitrogen fertilization levels on silage maize yield and soil fertility was investigated. Based on a field trial in Bottelare (Belgium), during the period 2007–2015, it was concluded that for each tillage system higher nitrogen levels resulted in a higher yield. In addition, the highest yield was achieved for the conventional tillage system, the yield gain for mouldboard ploughing varied between 13% (2015) and 71% (2012) compared to zero tillage. In case reduced tillage was adopted, the yield loss compared to mouldboard ploughing varied between 6% (2013 and 2015) and 24% (2012). Furthermore, it seemed that the accumulated temperature during the growing season and rainfall around flowering were decisive in determining maize yield. Additionally, rainfall in the period 60 days post sowing was significantly negatively correlated with the yield from the zero tillage plots, whereas in case tillage was adopted no correlations with rainfall 60 days post sowing were detected. Concerning the soil organic carbon content and the amount of earthworms, no clear trends could be observed. Zero tillage resulted in high weed pressure and caused soil compaction. So, in this trial, under humid conditions, the less labor intensive zero tillage system did not result in competitive maize yields. In conclusion, reduced tillage methods offer opportunities for maize cultivation in Belgium. This method of farming resulted in a lower yield, however, the difference with mouldboard ploughing was not significant. Therefore, adopting a reduced tillage system can be seen as a valid alternative for ploughing as this tillage system ensures a sustainable environment.